Current status of municipal solid waste management practise in FCT Abuja. - Ayuba, Kadafa Adati; Abd Manaf, Latifah; Abdullah Ho, Sabrina; Sulaiman, Wan Nor Azmin (Maxwell Science Publication, 2013)
Municipal solid waste management constitutes one of the most crucial health and environmental problem facing African cities. Most cities spend 20-50% of their annual budget on solid waste management and only 20-80% of the waste is collected. This study examines the current status of municipal solid waste management within Federal Capital Territory Abuja (FCT Abuja) and aims to identify the current challenges and areas requiring improvement. The data collection is in stages, using an in tegrative approach via semi st ructured interview and field observations. The qualitative data was analyzed descriptively, while the quantitative data was analyzed using basic statistics. Bases on the finding it is concluded that municipal solid waste management is a serious issue due to its human health and environmental sustainability implications, that has yet to be properly address within the FCT Abuja.